2020
DOI: 10.12688/wellcomeopenres.15531.2
|View full text |Cite
|
Sign up to set email alerts
|

Foot thermometry with mHeath-based supplementation to prevent diabetic foot ulcers: A randomized controlled trial

Abstract: Background: Novel approaches to reduce diabetic foot ulcers (DFU) in low- and middle-income countries are needed. Our objective was to compare incidence of DFUs in the thermometry plus mobile health (mHealth) reminders (intervention) vs. thermometry-only (control). Methods: We conducted a randomized trial enrolling adults with type 2 diabetes mellitus at risk of foot ulcers (risk groups 2 or 3) but without foot ulcers at the time of recruitment, and allocating them to control (instruction to use a liquid cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…The reference is a corresponding area on the contralateral foot. It is noteworthy that the temperatures of these areas do not differ by more than 1ºC 5 - 6 and a number of studies suggest that differences ≥ 2.2ºC in temperature can be considered a risk for ulceration 11 , 16 - 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The reference is a corresponding area on the contralateral foot. It is noteworthy that the temperatures of these areas do not differ by more than 1ºC 5 - 6 and a number of studies suggest that differences ≥ 2.2ºC in temperature can be considered a risk for ulceration 11 , 16 - 18 .…”
Section: Introductionmentioning
confidence: 99%
“…33 Data from a recent trial confirm that text and voice reminders in using thermometry do not affect adherence and outcome. 37 This may be inherent to this treatment approach and addresses an important barrier to implementation.…”
Section: Discussionmentioning
confidence: 99%
“…41 Based on this finding, a randomized controlled trial in Peru implemented the use of thermometry in 172 participants from two public national hospitals and one study arm was supplemented with a mHealth intervention involving SMS and voice messages. 42 It was found that 90% of the participants who returned their logbooks reported adherence to temperature measurement above 80%. However, the mHealth arm was not effective to reduce the incidence of diabetic foot ulcers.…”
Section: Technology To Prevent Diabetes Complications Perumentioning
confidence: 98%
“…However, the mHealth arm was not effective to reduce the incidence of diabetic foot ulcers. 42 This study faced some challenges, including the high proportion of people with diabetes that did not know how to open an SMS message. Trying to overcome this barrier, voice messages were also considered in the study design.…”
Section: Technology To Prevent Diabetes Complications Perumentioning
confidence: 99%